Analysis of Teacher Responses to Curriculum Changes and Its Implications in the Learning Process - Catur Wulandari; Syarwani Ahmad; Sri Wahyu Indrawati (PPSDP International Journal of Education, 2026)
The purpose of this study is to evaluate teachers’ responses to curriculum changes and their impact on the teaching and learning activities at SMA Negeri 7 Prabumulih. Curriculum change is one aspect of the dynamics of the educational system that requires readiness and adjustment from educators who play an active role in the field. This study employed a qualitative approach with a descriptive qualitative method. Data were collected through in-depth interviews, observations, and document analysis involving several teachers from various subject areas at the school. The findings show that teachers’ responses to curriculum changes are diverse, ranging from positive responses such as enthusiasm and readiness to adapt to negative responses such as confusion and rejection, caused by a lack of socialization and training. Some teachers faced challenges in understanding the content of the new curriculum and in applying a competency-based approach to learning. The consequences of these responses are apparent in the pedagogical approaches employed, the attainment of educational goals, and the students’ motivation to learn. This study suggests the necessity for ongoing training, rigorous mentoring, and efficient communication between policymakers and curriculum implementers in educational institutions to guarantee effective curriculum implementation and a beneficial influence on the quality of learning.